2020
DOI: 10.3393/ac.2019.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Oncologic Outcome of Postoperative Complications After Colorectal Cancer Surgery

Abstract: Purpose: The impact of postoperative complications on long-term oncologic outcome after radical colorectal cancer surgery is controversial. The aim of this study was to examine the risk factors and oncologic outcomes of surgery-related postoperative complication groups.Methods: From January 2010 to December 2010, 310 patients experienced surgery-related postoperative complications after radical colorectal cancer surgery. These stage I–III patients were classified into 2 subgroups, minor (grades I, II) and majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…The prognosis of CRC patients was currently concentrated by surgeons. It was revealed that the OS and DFS of CRC patients were affected by age, underlying diseases, tumor staging, and postoperative complications, which was largely consistent with our conclusions [ 30 , 31 ]. Some previous studies did not find an association between the waiting time and survival [ 11 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…The prognosis of CRC patients was currently concentrated by surgeons. It was revealed that the OS and DFS of CRC patients were affected by age, underlying diseases, tumor staging, and postoperative complications, which was largely consistent with our conclusions [ 30 , 31 ]. Some previous studies did not find an association between the waiting time and survival [ 11 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…Postoperative COVID-19 infection was significantly associated with mortality (adjusted odds ratio, 16.90; P < 0.001), which required surgeons to undertake stringent mitigation measures [ 27 ]. Furthermore, the leakage rate presented in this study was comparable to those of around 10% reported in the pre-pandemic era [ 37 38 ]. In addition, a further study reported a 10-fold increase in mortality among symptomatic COVID-19 patients but only a 2-fold increase in asymptomatic patients after gastrointestinal surgery.…”
Section: Resultssupporting
confidence: 84%
“…In contrast, Mark et al reported similar oncological results after resection for rectal cancer among patients who had major complications, those who had minor complications and those without complications [ 19 ]. Oh et al reported similar oncological results in patients with major (CD grade III or IV) or minor (grade I or II) complications after colorectal cancer surgery [ 24 ]. In the present study, RFS did not differ between patients who developed major SSI and those who developed minor SSI.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have usually included both patients after open surgery and those after laparoscopic surgery [ 14 , 15 , 19 24 , 30 32 ]. However, laparoscopic surgery has been applied for the majority of elective resections for colorectal cancer in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation